If you see a kitten - Butler, John, 1952- (London : Puffin, 2002)
Illustrations and brief text present appropriate responses to a variety of animals, from pudgy pigs to slithery snakes.
"First published in Great Britain in 2002 by the Penguin Group"--T.p. verso.
2.9
K-3
Keywords: Animals -- Juvenile fiction; Animals -- Fiction; Board books; Animals -- Fiction